The Impact of Digital-Based Mind Map on Creative Thinking Skills in Civic Education Learning - Syahputri, Neillisa Regga; Murdiono, Mukhamad (Jurnal Pendidikan Indonesia, 2022)
Students' creative thinking ability is low when using conventional learning media. Thus, the Civics learning process requires innovative learning media such as digital-based mind maps to improve students' creative thinking skills. This study aims to analyze the effect of digital-based mind map media on the creative thinking skills of class X students in Civics learning in vocational high schools. This research is a quasi-experimental research with a quantitative approach. The population in this study found 477 students using simple random sampling. This study used a test instrument in the form of an essay. Data collection was used for pretest and posttest. Hypothesis testing using t-test analysis with a significance level of 5%. The sample was determined through a random sampling technique which collected 62 students who were divided into two classes. The results showed that the posttest scores were more significant. Therefore, it can be said that there is a significant effect of digital-based mind maps on the creative thinking skills of class X students in Civics learning in SMK. Digital-based mind map media can improve students' creative thinking skills. It is expected that teachers use mind map media in learning civics education.